Religious reform - Hamzah, Dyala (The Oxford Handbook of Contemporary Middle Eastern and North African History, 2020)
The Oxford Handbook of Contemporary Middle-Eastern and North African History critically examines the defining processes and structures of historical developments in North Africa and the Middle East over the past two centuries. The Handbook pays particular attention to countries that have leapt out of the political shadows of dominant and better-studied neighbours in the course of the unfolding uprisings in the Middle East and North Africa. These dramatic and interconnected developments have exposed the dearth of informative analysis available in surveys and textbooks, particularly on Tunisia, Libya, Yemen, Bahrain and Syria.
Keywords: History / Africa / General; History / Middle East / General; History / Modern / 20th Century / General

Foundations of Religious Reform (Islah) and Cultural Revival (Nahda) - Hamzah, Dyala (The Oxford Handbook of Contemporary Middle Eastern and North African History, 2020)
The Oxford Handbook of Contemporary Middle Eastern and North African History critically examines the defining processes and structures of historical developments in North Africa and the Middle East over the past two centuries. The Handbook pays particular attention to countries that have leapt out of the political shadows of dominant and better-studied neighbours in the course of the unfolding uprisings in the Middle East and North Africa. These dramatic and interconnected developments have exposed the dearth of informative analysis available in surveys and textbooks, particularly on Tunisia, Libya, Yemen, Bahrain and Syria
Keywords: Africa, North; Handbooks and manuals; History; Middle East; North Africa; Politics and government